Future designers as actors of change : exploring design education scenarios focused on social innovation and sustainability - Rocha, Hugo (2020)
ABSTRACT : This paper, part of a Ph.D. in Design research, focused on discussing the role of Design Education on training future designers to be actors of change. It describes the methodology of a workshop for design students during the Design Week of Mérida, at Universidad de Extremadura – Spain. The workshop discussed the point of view of students in problem-solving, and what they believe to be the skills, methods, and partnerships for design to achieve such a change in its approach and how Design Education plays a part in preparing the future genera_on of designers to tackle social innovation and sustainability problems. The results showed how these particular group of future designers see as crucial in the given context and the possibilities for improvement on a system that struggles to be resilient and respond at a faster pace.